2021
DOI: 10.4236/ojgen.2021.114011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Investigation of Genetic Signatures of Selection in </i>Plasmodium falciparum</i> Actin-Binding Protein Coronin, Cysteine Desulfurase, and Plasmepsin 2 Gene in Mbita Field Isolates, Western Kenya

Abstract: Background: Plasmodium falciparum (Pf) resistance to antimalarial drugs is a major impediment to malaria control. The Pf.Kelch 13 (PfK13) gene has been largely reported to be associated with artemisinin resistance. However, recent studies have shown artemisinin resistance without Kech13 mutations suggesting the implication of others genes in artemisinin resistance. In this current study, we focused on mutations in Pf.actin-binding protein coronin, Pf.cysteine desulfurase and Pf.plasmepsin 2 gene, three putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…ART remains a crucial component of front-line antimalarial therapies, and its antimalarial efficacy must be protected. The current study underlines the potential threat of Pfcoronin -mediated resistance—in fact, the Pfcoronin R100K mutation was recently reported in Kenya, although artemisinin sensitivity/resistance was not assessed 45 . Other Pfcoronin polymorphisms were recently identified in Uganda 46 , and these polymorphisms were associated with ART resistance.…”
Section: Discussionmentioning
confidence: 80%
“…ART remains a crucial component of front-line antimalarial therapies, and its antimalarial efficacy must be protected. The current study underlines the potential threat of Pfcoronin -mediated resistance—in fact, the Pfcoronin R100K mutation was recently reported in Kenya, although artemisinin sensitivity/resistance was not assessed 45 . Other Pfcoronin polymorphisms were recently identified in Uganda 46 , and these polymorphisms were associated with ART resistance.…”
Section: Discussionmentioning
confidence: 80%
“…Such frequencies can be attributed to natural genetic variability, frequently observed in the integrase gene [ 35 , 44 ]. The oscillation of the frequency of the unknown-effect polymorphism mutations may result from genetic drift [ 45 ] since HIV-1 is subject to genetic variability. Further investigations are required to elucidate the association of these unknown mutations with INI-based regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The protein is conserved, and is expressed in the merozoite's periphery and also localized in late schizogony [50]. The coronin protein contains β-propeller domain like PfKelch13 protein [31] and it processes WD40 repeats (repetitive residues composed of tryptophan (W) -aspartic acid (D) at the Cterminus while having glycine (G) -histidine (H) at the N terminus) spanning the β-propeller domain which serves protein-DNA and protein-protein interaction and is also involved in multiples functions such as chemical inhibitors pathways, regulation of transcription, signal transduction [51,52,41] Pfcoronin is also implicated in vesicular transport, cytoskeletal motility F-actin binding and its structural organisation [31]. These functions highlight the prominent role of Pfcoronin protein in the P.falciparum parasite.…”
Section: Discussionmentioning
confidence: 99%
“…The protein is involved in the Ironsulphur biosynthesis and its delivery to different metabolic pathways for instance the Fe-S complex which is modulated in apicomplexans during drug resistance, and stress conditions [32] In P.falciparum, the iron homeostasis is substantive for blood-stage parasite development and is implied in the mechanisms of quinolones drug, _ the lumefantrine drug family [32]. Moreover, many important features were predicted in the cysteine desulfurase protein including Aminotran_5 domain, disordered regions covering low complexity motifs [41] those functions include adhesion, signal transduction, molecular recognition, interaction with phospholipid bilayers, protein modi cation, and modulation of protein translation [40,54] Pfplasmepsin 2 gene was found to be the less polymorphic gene in copy number variation, in total 6 isolates showed copy number variation. However, the highest CNVs detected in this study was found in the Pfplasmepsin 2 gene, three isolates (OS062/17, KM019/18, and AL106/16) showed (9.63, 9.41 and 9.18 copies) of plasmepsin 2 gene respectively (Fig 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation